2009
DOI: 10.1007/s00787-009-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and cognitive phenotype in children and adolescents with myotonic dystrophy

Abstract: Myotonic dystrophy type 1 (DM1) is the most frequent inherited neuromuscular disorder. The juvenile form has been associated with cognitive and psychiatric dysfunction, but the phenotype remains unclear. We reviewed the literature to examine the psychiatric phenotype of juvenile DM1 and performed an admixture analysis of the IQ distribution of our own patients, as we hypothesised a bimodal distribution. Two-thirds of the patients had at least one DSM-IV diagnosis, mainly attention deficit/hyperactivity disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 50 publications
3
40
0
5
Order By: Relevance
“…Congenitally affected fetuses are associated with excess amniotic fluid and decreased movement [56] [57], and occur almost exclusively from maternal transmissions (although there are exceptions [58]). The infantile and juvenile forms of DM1 are less severe than congenital, but still exhibit many of the same features, in particular, cognitive challenges [59] [60]. Severe myotonia is also much more prominent in the juvenile form [55].…”
Section: Repeat Range Penetrance Age Of Onset and Relationship mentioning
confidence: 99%
“…Congenitally affected fetuses are associated with excess amniotic fluid and decreased movement [56] [57], and occur almost exclusively from maternal transmissions (although there are exceptions [58]). The infantile and juvenile forms of DM1 are less severe than congenital, but still exhibit many of the same features, in particular, cognitive challenges [59] [60]. Severe myotonia is also much more prominent in the juvenile form [55].…”
Section: Repeat Range Penetrance Age Of Onset and Relationship mentioning
confidence: 99%
“…For the children that pass the critical neonatal period, the developmental profile (especially motor and language skills) improved in early childhood and apparently faster in boys (Prasad et al, 2016). However, moderate to severe intellectual disabilities, reduced IQ-values, speech and language delay, deficit in visuospatial and/or visuo-constructive skills, attention deficit with or without hyperactivity disorder (ADHD), autism spectrum disorder, problems with communication and social anxiety have been reported by several authors in DM1 childhood patients (Angeard et al, 2007, 2011; Meola and Sansone, 2007; Ekström et al, 2008, 2009; Douniol et al, 2009, 2012). Interestingly, a survey distributed to parents of affected child revealed that problems with communication and fatigue appeared to have the greatest impact on childrens' lives (Johnson et al, 2014).…”
Section: Neuropsychiatric Cognitive and Other Neurological Symptomsmentioning
confidence: 99%
“…Douniol et al [21] ont essayé de comprendre la variabilité dans la distribution des QI des sujets porteurs de la forme infantile de la DM1 en réalisant une analyse des différentes études existantes. Partant de la distribution bimodale, ils ont ainsi distingué deux phénotypes au sein même de la forme infantile : un premier sous-groupe caractérisé par une déficience intellectuelle modérée, un retard du langage et moteur durant l'enfance, des difficultés d'apprentissage majeures, une somnolence avec de possibles troubles de la vigilance et une transmission de la maladie majoritairement d'origine maternelle ; un deuxième sous-groupe avec une intelligence normale/subnormale, une dissociation entre les échelles de QI (où majoritairement le QI verbal > QI performance), des difficultés d'apprentissage modé-rées, des déficits attentionnels et visuo-spatiaux et un mode de transmission majoritairement paternel.…”
Section: Fonctionnement Cognitif Dans La Forme Infantile De La Dm1unclassified
“…L'expérience clinique montre que les diagnostics basés sur la combinaison des informations provenant des parents, de l'histoire clinique et des observations cliniques sont significativement plus stables au cours du temps[20] que ceux obtenus à partir d'un seul outil. Douniol et al[21] avaient déjà soulevé cette problématique en présentant deux cas cliniques où les symptômes associés à la forme infantile de la DM1, comme le retard dans l'acquisition du langage, l'hypotonie et le retrait social, peuvent contribuer à une présentation d'un « tableau autistique » chez les jeunes patients DM1 qui n'était pas confirmé avec le temps.La grande variabilité d'expression des symptômes dans la population d'enfants avec TSA (l'absence du langage chez la plupart d'enfants TSA tandis que d'autres vont dévelop-per un langage sophistiqué ; certains enfants présentent des comportements d'automutilation ou d'agressivité extrême tandis que d'autres n'en ont pas ; les déficits sociaux peuvent également varier considérablement) se retrouve également chez les sujets DM1. Ainsi, dans l'analyse réalisée par Ekström et al[10], 4 groupes sont distingués :…”
unclassified